Interactions of Xanthomonas type-III effector proteins with the plant ubiquitin and ubiquitin-like pathways - Üstün, Suayib; Börnke, Frederik (Frontiers in Plant Science, 2014)
In eukaryotes, regulated protein turnover is required during many cellular processes, including defense against pathogens. Ubiquitination and degradation of ubiquitinated proteins via the ubiquitin – proteasome system (UPS) is the main pathway for the turnover of intracellular proteins in eukaryotes. The extensive utilization of the UPS in host cells makes it an ideal pivot for the manipulation of cellular processes by pathogens. Like many other Gram-negative bacteria, Xanthomonas species secrete a suite of type-III effector proteins (T3Es) into their host cells to promote virulence. Some of these T3Es exploit the plant UPS to interfere with immunity. This review summarizes T3E examples from the genus Xanthomonas with a proven or suggested interaction with the host UPS or UPS-like systems and also discusses the apparent paradox that arises from the presence of T3Es that inhibit the UPS in general while others rely on its activity for their function.